Constitución E Implementación De Una Empresa De Protección Y Guardianía Para La Provincia De Loja” - Torres Torres, Verónica Alexandra (2016)
Present investment project is based on the provision of protection and private security staff in the main districts of the province of Loja such as: Loja, Catamayo, Bald, Celica and Chaguarpamba, with the aim of improving the quality of life population by offering security systems that allow them to feel and be more secure and calm. Thus was born the idea of providing private security services custom and affordable costs for all lojana citizenship. Furthermore, this project integrates private security services for both households and businesses in general and larger firm. To start this project, a market study was performed in order to meet supply and demand, to obtain demand a sample of 299 surveys was applied to families and 83 economic entities in order to identify key security needs private. The survey of supply is instead applied to 8 security companies that provide this service in the local market in order to know the number of services that supply and demand determine unmet . So a marketing plan in which services, price, place, promotion and advertising in which the company was based was defined was also performed. A technical study in which it was considered that this project be implemented in the province of Loja was performed, it will have a lifespan of 10 years and 365 days. In terms of installed capacity is obtained according to the number of employees, safety equipment and based on work schedules, obtaining that the company will supply 10% of the unmet demand. In terms of capacity utilization is expected to work for the first year 85% of installed capacity and gradually rising to reach 100% in the fifth year. Well as micro and macro location will be located in the area “El Valle "from the city of Loja, for easy location, leasing costs, infrastructure and access to basic necessities. The flow of services programs Monitoring alarms, CCTV, neighborhood, business and residential guardianship to provide the entity was also developed. Then the legal administrative study in which the company is defined as a limited liability company as provided by law and details all the requirements that you must meet to legally form the same , including the minutes of association with the name is of 10 partners and number of shares in the company. Also the chart shows: structural, functional and positional shaped by the level, director, officer , consultant, support , administrative and operational , so we can also see the philosophy of the company with its own logo, mission, vision , objectives and values institutional , and finally within this study manual detailing work functions that each employee must meet and the rules that should govern all those involved in this institution was defined . To calculate the financial study the initial investment of $ 150,527.46 consisting of current fixed assets, deferred and found the same to be financed 57% by contributions from partners and 43% with a loan from the CFN. Moreover also finds the fixed and variable costs, the selling price each service and revenue ($389,502.33) to be obtained annually. The financial evaluation a positive NPV of $ 207,422.67 a cost benefit ratio of 1.20 , so the IRR is $ 35.5% , a recovery period of 2 years , 9 months and 23 days, sensitivity was obtained high costs increased 6.43 % and sensitivity by decreasing income of 5.43 % that demonstrate the feasibility of the project. Then conclusions and recommendations are made based on the results obtained in studies. Emphasizing that should be taken into account to optimize the time of starting the project operations of the company. Finally we annexes that support the different content expressed therein. The support that is provided with this project is to contribute to the development of the local economy through a proposed investment project based on the provision of private security services for the province of Loja.